Subdifferentials and Coderivatives of Efficient Point Multifunctions in Parametric Convex Vector Optimization - An, Duong Thi Viet; Hung, Nguyen Huy; Van Tuyen, Nguyen (Journal of optimization theory and applications, 2024)
In this paper, by revisiting coderivative calculus rules for convex multifunctions in finite-dimensional spaces, we derive formulae for estimating/computing the basic subdifferential and the coderivative of the efficient point multifunction of parametric convex vector optimization problems. These results are then applied to a broad class of conventional convex vector optimization problems with the presence of operator constraints and equilibrium ones. Examples are also designed to analyze and illustrate the obtained results.